A Systematic Review of the Frequency of Regulatory T Cells in Hepatitis B and Hepatitis C - Tri Nugraha Susilawati; Atik Susianto (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: Regulatory T cells (Tregs) play an important role in sustaining the hepatitis B and C viruses (HBV and HCV) persistence and protecting the liver tissues from cytokine-associated detrimental effects through unclear mechanisms. This paper aims to review the frequency of Tregs during the course of HBV and HCV infection.Method: Electronic databases were searched to identify studies investigated the frequency of intrahepatic and peripheral Tregs of the patients infected with HBV and/ or HCV.Results: The majority of studies reported the increase of intrahepatic and peripheral Tregs in acute and chronic infection of HBV and HCV. The decrease of peripheral Tregs occurred in patients with chronic hepatitis B who respond to interferon α or nucleos(t)ide analogues treatment as well as those with chronic hepatitis C who were treated with interferon, ribavirin or liver transplantation.Conclusion: Infection with HBV and HCV appears to induce the production of Tregs in blood and hepatocytes whereas treatment may decrease Tregs levels. As the optimum balance between regulatory and effector T during HBV and HCV infection is crucial for preventing liver damage, further studies should be directed on the development of Tregs during HBV and HCV infection as well as their involvement in immunomodulatory strategies for combating HBV and HCV.